Advances in genetics. - Kumar, Dhavendra (Advances in genetics, 2019)
'Advances in Genetics, Volume 103, ' provides the latest information on the rapidly evolving field of genetics, presenting new medical breakthroughs that are occurring as a result of advances in our knowledge of the topic. The book continually publishes important reviews of the broadest interest to geneticists and their colleagues in affiliated disciplines, critically analyzing future directions. Key Features: Critically analyzes future directions for the study of clinical genetics; Written and edited by recognized leaders in the field; Presents new medical breakthroughs that are occurring as a result of advances in our knowledge of genetics. Readership: Molecular geneticists, clinical geneticists, neurologists, neuroscientists, molecular biologists, and biochemists. --